EKSPERIMENTASI PENDEKATAN MATEMATIKA REALISTIK DENGAN PEMBERIAN TUGAS DITINJAU DARI KEMAMPUAN AWAL TERHADAP HASIL BELAJAR MATEMATIKA - Fadila, Abi (JURNAL E-DUMATH, 2015)
AbstractThe aims of this research are to find out the different effect of each categories of realistic mathematic approach with task or without task, initial capability characteristics, and their interaction towards students mathematics learning results used realistic mathematic approch. The research used to quasi experimental with 2x2 factorial design. The samples of the research were taken by cluster random sampling technique. Based on hypothesis test, it can be conclude that the learning results used Realistic Mathematics Approach tith task have a better than without task, the learning result of the students who have good initial capability is better than lowerinitial capability, and there is interaction between the realistic mathematic approach with initial capability characteristics.Â Key Words: Realistic Mathematics Approach; Initial Capability; Learning Result